DISPUTE RESOLUTION METHODS IN PROJECT TEAM MANAGEMENT IN INVESTMENT PROJECTS - Akramov Azamat Ramziddinovich (Journals Park Publishing, 2024)
The article examines the opinions of the world's leading scientists on ways to resolve conflicts in the management of the project team in investment projects , identifies the conflicts that cause conflicts in the management of the project team in investment projects, systematizes the theories of human resources management, makes reasonable conclusions and suggestions on the ways to resolve conflicts in the management of the project team in investment projects developed.
Keywords: Investment, style, project team, personnel management